Case Report: Successful Treatment of Kaposi’s Sarcoma With Anlotinib in an HIV-Negative Patient After the Treatment of Drug Reaction With Eosinophilia and Systemic Symptoms Accessory Tragus - Lin, Min; Luo, Renwei; Zhang, Peng; Xiao, Zhixun; Gong, Ting; Ji, Chao (Frontiers in Medicine, 2022)
Kaposi’s Sarcoma (KS) is a neoplasm derived from endothelial cells and is associated with human herpesvirus-8 (HHV-8) infection. It is mostly seen in patients suffering from AIDS and/or chronic immunosuppression. Currently, systemic chemotherapy is the primary treatment option for the advanced KS. However, there is no consensus on the treatment of KS. In this case, an 84-year-old man with a history of psoriasis developed multiple painful dark purple nodules on the trunk and extremities during the treatment of drug reaction with eosinophilia and systemic symptoms (DRESS). KS was confirmed by the skin biopsy, and the immunohistochemical staining demonstrated the positivity for HHV-8 while the anti-HIV test was negative. The patient then received anlotinib treatment, a tyrosine kinase inhibitor, for 5 months, and his skin lesions subsided. This case indicates that anlotinib may be a potential treatment option for KS.